2023
DOI: 10.1111/phn.13215
|View full text |Cite
|
Sign up to set email alerts
|

Ecological study: MSM sex worker advertising amidst Monkeypox in three U.S. cities

Abstract: The 2022 monkeypox (MPX) outbreak was a source of consternation and stress among men who have sex with men (MSM)—the population disproportionately affected by the recent MPX outbreak. Individuals at high‐risk for MPX (e.g., MSM, sex workers) were prioritized for vaccination during early state and city health department vaccine initiatives across the U.S., but little is known about how the MSM sex work market was affected by the MPX outbreak in U.S. cities where MPX incidence was particularly high. To better ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…of MSM had declared that they wanted to accept another income-generating activity to replace activities linked to their MSM status. This willingness to change activity in favor of another income-generating activity could lead to the hypothesis that MSM activities would constitute an income-generating activity, and These MSM are therefore workers in the informal sector, like female sex workers and GBV is then occupational hazard [9]. In addition, the clandestine activity of MSM makes them hidden GBV victims [8] [26] [28], and as workers in the informal sector are not covered by occupational medicine, implementing preventive actions for them becomes complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of MSM had declared that they wanted to accept another income-generating activity to replace activities linked to their MSM status. This willingness to change activity in favor of another income-generating activity could lead to the hypothesis that MSM activities would constitute an income-generating activity, and These MSM are therefore workers in the informal sector, like female sex workers and GBV is then occupational hazard [9]. In addition, the clandestine activity of MSM makes them hidden GBV victims [8] [26] [28], and as workers in the informal sector are not covered by occupational medicine, implementing preventive actions for them becomes complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have recently shown that MSM sex workers have a higher risk of contracting HIV than other MSM and even female sex workers [5] [6] [7]. In addition, clandestine activities linked to the fear of stigmatization make it difficult to assess the contamination risks of MSM sex workers [8] [9], who are therefore workers in the informal sector. These findings call for targeted studies to identify MSM who are sex workers among all MSM, in order to adapt control strategies.…”
Section: Introductionmentioning
confidence: 99%